Convergence of east-west poetics : Williams's negotiation with the Chinese landscape tradition - Yang, Zhanghui, 1982- (New York, NY : Routledge, 2024)
"The present book examines Williams's negotiation with cultural modes and systems of Chinese landscape tradition in his landscape writing. Focusing on Walliams's landscape modes of landscape with(without) infused emotions, the book builds a linkage between their interactions with Chinese landscape aesthetics and shows how these conversations helped shape Williams's cross-cultural landscape poetics. The exploration of Williams's experiment with the Chinese serene interplay of self and landscape, the interfusion of scene and emotion, an idea of seeing under the perspective of Wang Guowei's theory of jingjie, and the poetic space of frustration and completion in the context of space and human geography, expand the understanding of a cross-cultural landscape tradition developed by Williams through bringing into focus the convergence of East-West poetics"--
Keywords: Williams, William Carlos, -- 1883-1963 -- Criticism and interpretation; Landscapes in literature; American literature -- Chinese influences; LITERARY CRITICISM / General; LITERARY CRITICISM / American / General; LITERARY CRITICISM / Asian / Chinese